AOTT 2022
DOI: 10.5152/j.aott.2022.21190
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the clinical and radiographic outcomes of plate fixation versus new-generation locked intramedullary nail in the management of adult forearm diaphyseal fractures

Abstract: Objective: This study aimed to compare functional and radiographical outcomes following intramedullary nailing (IMN) versus plate and screw osteosynthesis in managing patients with diaphyseal forearm fractures. Methods: Forty-six patients (27 male, 19 female) were included in this retrospective study. Of these, 25 were treated with plate osteosynthesis and 21 with IMN. The mean age was 32.4 (range, 19–67) years in the plate group and 28.8 (range, 18–64) years in the IMN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…In our study, the right side was more common in both groups. Ambhore et al [2] and Polat et al [20] studies also had a majority of fractures in the right forearm, which is correlated with our study. In this study, both groups were statistically similar in terms of age, gender, and side of injury.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the right side was more common in both groups. Ambhore et al [2] and Polat et al [20] studies also had a majority of fractures in the right forearm, which is correlated with our study. In this study, both groups were statistically similar in terms of age, gender, and side of injury.…”
Section: Discussionsupporting
confidence: 92%
“…In a study conducted by Polat et al 18 with a group of 46 patients who underwent new-generation IMN and plate osteosynthesis for forearm fractures, the mean union time was 10.9 weeks in the IMN group and 13.2 weeks in the plate group, with union being faster among patients who underwent IMN. In their study including 100 patients, Savajiyani et al 19 achieved adequate union in 88 cases using IMN and reported union times compatible with other studies in the literature.…”
Section: Discussionmentioning
confidence: 97%
“…IM nail techniques minimize damage to soft tissue and the periosteum and promote secondary callus formation, providing a better alternative. The recently developed interlocking IM nailing method prevents not only rotational stability of the fracture, but also bone shortening [ 8 , 9 , 14 , 15 ]. Some researchers have suggested that comminuted fractures, segmental fractures, and fractures near the diaphyseal-metaphyseal junction are appropriate indications for interlocking IM nailing in forearm fractures [ 3 , 5 , 7 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, IM nailing alone resulted in a higher incidence of non-union and changes in bone length. Polat et al [ 14 ] compared two groups who were treated with IM nails and plates, finding that distant locked IMNs are a viable alternative to ORIF with plate osteosynthesis with similar healing rates, functional scores, and shorter operative times. In that study, there were only three patients with diaphyseal fractures, making it difficult to conclude that this method is also useful for treating segmented fractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation